Mechanism of Learning Process (Global Journal of Human-Social Science, 2017)
An attempt was made to understand mechanics of learning The information showed that children generally use right brain to learn while adults use left brain Learning is a function of conscious mind subconscious mind intellect and ego The conscious mind learns with the help of sensory organs the capacity of which is limited and its memory is also short-lived To convert the short term memory into long term one the material learnt by conscious mind has to be driven to sub-conscious mind by repetitions More the repetitions more strong the long term memory The knowledge in the sub-conscious mind can also be stored if it is linked with things that are easy to remember However the recalling of information from subconscious to conscious mind is not possible in a disturbed state of mind To alleviate this problem a silent exercise consisting of doing nothing for 10-15 minutes duration is described Besides the silent exercise also helps in increasing the capacity of conscious mind to understand and learn The intellect is the discriminative faculty of mind Its main job is to protect the ego If a learner considers himself to be excellent intellect will do every effort to protect his excellence The chanting of gayatri mantra is also advised as it sharpens the intellect of the learner